Osmotic Stress Induces Rapid Activation of a Salicylic Acid–Induced Protein Kinase and a Homolog of Protein Kinase ASK1 in Tobacco Cells - Mikołajczyk, Monika (American Society of Plant Biologists, 2000)
In tobacco cells, osmotic stress induced the rapid activation of two protein kinases that phosphorylate myelin basic protein. Immunological studies demonstrated that the 48-kD kinase is the salicylic acid–induced protein kinase (SIPK), a member of the mitogen-activated protein kinase family. SIPK was activated 5 to 10 min after the cells were exposed to osmotic stresses, and its activity persisted for ∼30 min. In contrast, the 42-kD kinase was activated within 1 min after osmotic stress, and its activity was maintained for ∼2 hr. Moreover, in addition to myelin basic protein, the 42-kD kinase phosphorylated casein and two transcription factors, c-Jun and ATF-2. This latter enzyme was inactivated by a serine/threonine–specific phosphatase but, unlike SIPK, was not affected by a tyrosine-specific phosphatase. After the 42-kD kinase was purified to apparent homogeneity, tryptic peptide analysis indicated that it is a homolog of Arabidopsis serine/threonine kinase1 (ASK1).